PENGARUH QUALITYOF WORK LIFE TERHADAP KINERJA PEGAWAI KELURAHAN (Studi di 6 Kelurahan Pada Kabupaten Barito Utara) - Isma’il; Laila Refiana Said (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This is study aims to determine and analyze the influence of the the independent variables i.e. the Career Development as part of Quality Of Work Life (X1), and the Conflict Resolution as Part of Quality of Work Life (X2), either simultaneously or partially, towards the dependent variable, i.e. Officer Performance (Y), in six villages, namely villages of Jingah, Jambu, Lanjas, Melayu, Lahei I and II Lahei in the Regency of Barito Utara. The research method used used was quantitative research which was explanatory, with the number of population was 48 officers in six sample villages, namely the villages of Jingah, Jambu, Lanjas, Melayu, Lahei I and Lahei II in the Regency of Barito Utara. The sampling technique used was Census method. The variable measurement used was the Likert scale with a scale rating from in to 5. To analyze the influence of the variables of the Career Development, as part of the Quality Of Work Life (X1), and Conflict Resolution, as part of the Quality Of Work Life (X2), towards the performance Officer (Y) the technique multiple linear regression statistics technique was used. The results of this study concluded thaht the variables the Career Development as part of the Quality of work Life (X1), and Conflict Resolution aspart of the Quality of Work Life (X2), influence simultaneously the variable of the Officer Performance (Y). The variables of the Career Development as part of the Quality Of Work Life (X1), does not influence on the Officer Performance (Y) because the Career Development are not as being expected by the village officers, whereas of Conflict Resolution, as part of the Quality Of Work Life (X2), towards the performance Officer (Y).